The Usefulness of Accounting Information on Financial Instruments to Investors Assessing Non-Financial Companies. An Empirical Analysis on the Bucharest Stock Exchange - Maria Carmen Huian (Journal of Accounting and Management Information Systems (JAMIS), 2015)
The aim of this paper is to study the value relevance of IFRS-based accounting information regarding financial instruments provided by non-financial Romanian groups quoted on Bucharest Stock Exchange for the period 2011-2013. Data from both consolidated and parent-only accounts are tested using a modified Ohlson model to show the empirical correlation between stock market prices and accounting numbers. We find that at parent company level, the information about financial assets is more value relevant than the one about financial liabilities. At group level, investors rely mostly on information about financial assets, ignoring the one about financial liabilities. Moreover, results show the superiority of parent company's individual accounts over the consolidated ones in terms of value relevance of financial instruments information.
Keywords: M41; 650; financial instruments; value relevance; IFRS; regression analysis